2016
DOI: 10.1180/claymin.2016.051.3.08
|View full text |Cite
|
Sign up to set email alerts
|

Co-remediation of Ni-contaminated soil by halloysite and Indian mustard (Brassica junceaL.)

Abstract: The effects of increasing nickel contamination of soil on the update of selected microelements by Brassica juncea L. in the presence of raw halloysite (RH) and halloysite modified by thermal treatment (calcination) at 650°C (MH) were investigated experimentally. Such treatment causes partial dehydroxylation and enhances mineral-adsorption properties towards cations. In a vegetative-pot experiment, four different levels of Ni contamination, i.e. 0 (control), 80, 160, 240 and 320 mg kg−1 were applied in the form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 40 publications
(36 reference statements)
4
10
0
Order By: Relevance
“…The highest reduction of Zn contents (20%) was observed in the aboveground parts of the tested plant species grown in soil containing dolomite, as compared to the uncontaminated soil. These results were similar to another experiment conducted by Radziemska et al [3,14,29], where the heavy metal contents in the aboveground parts of Z. mays, B. juncea, and L. perenne were affected by the application of mineral sorbents (i.e., zeolite, halloysite, limestone, chalcedonite, and dolomite). The roots of the test plat contained 22% more Zn as compared to the control group when dolomite was applied to the soil.…”
Section: Zn Accumulation and Translocation Of F Rubrasupporting
confidence: 79%
See 1 more Smart Citation
“…The highest reduction of Zn contents (20%) was observed in the aboveground parts of the tested plant species grown in soil containing dolomite, as compared to the uncontaminated soil. These results were similar to another experiment conducted by Radziemska et al [3,14,29], where the heavy metal contents in the aboveground parts of Z. mays, B. juncea, and L. perenne were affected by the application of mineral sorbents (i.e., zeolite, halloysite, limestone, chalcedonite, and dolomite). The roots of the test plat contained 22% more Zn as compared to the control group when dolomite was applied to the soil.…”
Section: Zn Accumulation and Translocation Of F Rubrasupporting
confidence: 79%
“…The results of earlier experiments show a metal immobilizing effect on plant biomass after the application of mineral sorbents (i.e., halloysite, zeolite, limestone, and calcium oxide) in pot experiments [14][15]. The results showed that the growth of the tested plant was signifi -cantly affected by the dose of the Zn-contaminant and the applied amendments.…”
Section: Biomass Response Of F Rubra To Zn Contamination and Applicamentioning
confidence: 70%
“…In the work of Wyszkowski and Radziemska [2013a, 2013b, 2010, zeolite increased the average yield of aerial parts of oats, spring barley and maize grown in soil polluted with hexavalent chromium. The application of halloysite to nickel-contaminated soil increased the yield of Brassica juncea (L.) [Radziemska et al, 2016d].…”
Section: Resultsmentioning
confidence: 99%
“…LSD for: a -chromium form; b -chromium dose; c -kind of neutralizing substance; ** -significant at p = 0.01; * -significant at p = 0.05 whereas in excessive amounts, it may occur in plants in a cation form (Ni 2+ ) (Radziemska et al 2016b, Li et al 2015. In the series without alleviating substances, the average content of Ni in the above-ground parts of spring rapeseed was at a similar level in soils containing Cr(III) and Cr(VI), in contrast to the aftercrop -yellow lupine, where a higher average content of Ni in the plant occurred in pots with Cr(III).…”
Section: : Effect Of Cr(iii) and Cr(vi) Chromium (Iii) And (Vi) Contmentioning
confidence: 99%